Soil Destruction Level at Upstream of Cikapundung Sub Watershed on The North of Bandung Area - N. SUTRISNA; SANTUN R.P. SITORUS; KASDI SUBAGYONO (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2010)
The upstream of Cikapundung sub watershed is the high land which is located on the North of Bandung Area. The soil is fertile, therefore the land is used as farming. The agriculture land is slope and the farmers have not applied the technology of conservation yet, as the result the soil susceptible to erosion. Consequently it decreases the productivity of land. The objectives of study were: (1) to evaluate erosion (value and risk erosion) at the use of land existing and (2) to investigate soil destruction level by erosion and its impact to productivity of land at upstream of Cikapundung sub watershed. The research used survey method. The data consisted of secondary data and primary data. The secondary data was collected through desk study, whereas primary data was collected through interviewed farmers, the soil observation, and soil sample analyses that is included the contain of sand, dust, and clay; C-organic; and nutrient content (N, P, K, and Ca) at Laboratory. The data analysis was done according to descriptive. The result showed that the most soil erosion was at the type of vegetable land use which use intensively at slope 25-40%.Value erosion roundabout 22.57-597.76 ton ha-1 year-1 or 0.33-8.79 cm. Level of destruction soil by erosion at upstream of Cikapundung sub watershed majority was medium critic (the upper soil was loss >75%) and spread at some units land. During five years, the impact of erosion decreased C-organic 60.05%, N 44.7%, P 52.3%, K 24.7%, and Ca 27.2%. Productivity Potato decrease 60%, whereas cabbage 40%.